FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MODERASI - Kusumah, Olivia Christabella; Nariman, Augustpaosa (Jurnal Paradigma Akuntansi, 2025)
The purpose of this research was to obtain empirical evidence on the influence of liquidity and profitability variables on firm value with the CSR variable as the moderation. This study used secondary data which was tested using SPSS version 29. The research data came from companies in the food and beverage sub-sector from consumer goods industry companies listed on the IDX during 2019-2021, where sample selection used purposive sampling and a total of 21 companies were obtained. . The results obtained are that liquidity has no effect on firm value, profitability has a positive influence on firm value, CSR is not able to moderate the effect of liquidity on firm value, but CSR is able to moderate the effect of profitability on firm value.